Glorious Gardens : A Portfolio of Ideas for Planting & Design (London Conran Octopus Ltd, 1992)
"A celebration of garden styles and planting schemes with all the information needed to make such dream gardens a reality. The book presents photographs of 20 classic styles, each picture accompanied by analysis of how the effect has been achieved and how to recreate it, even in the smallest plot." --Publisher description.
Include Color Illustration, Acknowledgment and Index
Commentary by Greenoak, Francesca
Keywords: Landscape gardening -- Gardens--Design -- Gardens